P172 Implementation of alcohol screening in patients attending a large walk-in sexual health service within london. (18th May 2015) - Oxenham, Chantal; Guild, Alexander Campbell; Watfa, Salima; Dosekun, Olamide; Malek, Ramona; Hodson, Lydia; Wilkinson, Dawn
Abstract : Background: UK national guidelines advocate a role for sexual health services to offer routine screening for high-risk alcohol consumption in patients. Screening for alcohol misuse and offering brief interventions in this setting has been shown to be acceptable to clinicians and patients. In August 2014 the Fast Alcohol Screening Test (FAST) was incorporated into the sexual history proforma in a London Genitourinary Medicine (GUM) clinic. Aim: An audit was undertaken to assess the use of the FAST tool and management of patients with a positive FAST result. Methods: A retrospective case-notes review of randomly selected patients attending the GUM clinic in October 2014 was performed. Information was collected on patient demographics, sexual history, sexually transmitted infections, completion of FAST tool and action dependent on outcome of risk assessment. Results: 169 case notes were reviewed: 55% female and 45% male, mean age was 30 (range 17–74) years. The FAST tool was completed in 87% (147/169) of case notes. Of patients screened, 86% (127) identified as low risk, 10% (15) increasing and 4% (5) high risk (hazardous drinkers). Of hazardous drinkers, 90% (18) had a documented action for risk reduction; 56% (10) had verbal advice documented, 22% (4) accepted written advice, 22% (4) accepted referral to a sexual health advisor. Conclusion: Clinician completion of the FAST tool within the sexual history proforma in a busy clinic was high, with some scope for improvement. Of the relatively low number of hazardous drinkers identified, most accepted only brief verbal advice in clinic.